Complementary Role of Fishers’ Experiential Knowledge to Conventional Science in Terms of Species-Specific Biological Traits and Population Changes in Azorean Waters - Régis Santos; Ualerson Iran Peixoto; Morgan Casal-Ribeiro; Wendell Medeiros-Leal (Biology, 2023)
Combining scientific information with fishers’ perceptions may be a robust approach for directing decision-makers working with marine ecosystems. This is particularly the case when baseline data on a vulnerable stock are poor, as the integration of fishers’ experiential knowledge can help fill data gaps, as well as inform legitimate management actions, and empower fishing communities in resource management. This study aimed to analyze fishers’ knowledge regarding the biology (reproduction, growth, and maximum size) and temporal changes in the abundance and size of six commercially important marine species (red porgy Pagrus pagrus, veined squid Loligo forbesii, blue jack mackerel Trachurus picturatus, blackspot seabream Pagellus bogaraveo, blackbelly rosefish Helicolenus dactylopterus, and European conger Conger conger) in the Azores small-scale communities. Additionally, a comparison between fishers’ knowledge and available scientific information was performed to determine the former’s value and its possible complementarity with the latter. A total of 105 fishers were surveyed in the nine islands of the archipelago. The results demonstrated a reasonable level of agreement between the information from fishers and scientific literature on the species-specific spawning seasons and growth rates. The median values of size at maturity and maximum length were not statistically different between data sources. Most participants indicated size and abundance trends that were consistent with the literature. This study highlights the usefulness of fishers’ perceptions in improving knowledge about species characteristics and temporal changes in commercially exploited stocks, especially when scientific research is limited, but further research should be encouraged to improve the reliability and consistency of these results.